O efeito da estrutura da matriz na percepção de aves na paisagem - Giubbina, Marina Furlan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The increased demand for agricultural products results in intense habitat loss and fragmentation, causing spatial changes in landscapes and biodiversity loss. The intervening matrix, i.e. non-habitat environments surrounding habitat patches, can act as barrier in the movement of organisms between fragments, reducing the functional connectivity for many species. But the influence of matrix composition and its structure on fauna movement rarely has been quantified. Thus, this study aimed to evaluate the influence of the presence and structure of the matrix in the movement of two forest-dependent bird species: Thamnophilus caerulescens and Synallaxis frontalis. Twelve landscapes containing sugarcane and Eucalyptus matrices Using playback trials in the sinuosity the birds had the option of following the vocalizations from one point to another in the curve by two different routes, (1) a shorter one through the matrix and (2) another longer inside fragment's edge. The distances between the playbacks ranged from 30 to 130 meters. Control trials were done within the remaining, in which the vocalizations were first played at the forest edges. As the individuals answered the voalizations, the playback was reproduced 10 meters increasingly inside the remnant, observing the distances traveled by each species. Thus, through analysis of variance and GLMS, it observed that there is a greater preference by following the playback inside the forest edge than by the matrix. It was also found that there is a negative correlation between distance and probability to cross the matrix and the species followed playback at greater distances in control than in both routes. By comparing sugarcane and Eucalyptus it was found that the first was more permeable than the latter, demonstrating that the structure of the matrix interferes their permeability. The routes that individuals followed the playback differ between the matrices, and there was a greater expenditure of ...

O aumento da demanda de produtos agrícolas vem causando intensa perda e fragmentação de habitat, resultando em modificações espaciais na paisagem e perda de biodiversidade. As modificações no uso e cobertura do solo, causadas por atividades antrópicas, são chamadas de matriz e sua composição e estrutura podem gerar uma grande barreira na movimentação de organismos entre fragmentos, influenciando negativamente a conectividade funcional para muitas espécies. O experimento de playback tem se mostrado eficiente para realizar experimentos de movimentação de aves entre fragmentos para inferências sobre conectividade funcional e percepção da paisagem pelas espécies. Deste modo, este estudo teve como objetivo avaliar a presença e estrutura da matriz na movimentação na paisagem das espécies de aves Thamnophilus caerulescens (choca-da-mata) e Synallaxis frontalis (petrim). Doze paisagens contendo as matrizes cana-de-açúcar e Eucalyptus e fragmentos florestais configurados espacialmente contendo sinuosidades foram selecionados. Utilizando o método de playback nas sinuosidades as aves tiveram a opção de seguir as vocalizações de um ponto para outro da curva por uma rota mais curta atravessando a matriz e outra mais longa pela borda do fragmento. As distâncias entre os playbacks variaram de 30 a 130 metros. O controle foi realizado dentro dos remanescentes, no qual as vocalizações foram reproduzidas inicialmente na borda dos fragmentos e foi-se adentrando ao remanescente até à distância que os indivíduos cessaram as respostas. Assim, através de análises de variância, foi possível verificar que há maior preferência de seguir o playback pela borda do fragmento do que pelas matrizes. Também foi apurado que há uma correlação negativa entre distância e probabilidade de passagem pela matriz e que as espécies seguem o playback a distâncias maiores no controle do que em ambas as matrizes. Ao comparar cana-de-açúcar...
Keywords: Birds; Ave; Ecologia da paisagem; Biodiversidade